Comparison of Simultaneous Soil Profile N2O Concentration and Surface N2O Flux Measurements Overwinter and at Spring Thaw in an Agricultural Soil. Issue 1 (30th January 2014) - Risk, Neil; Wagner-Riddle, Claudia; Furon, Adriana; Warland, Jon; Blodau, Christian
Abstract : In cold climates, large emissions of N2 O have been found to occur from agricultural soils at spring thaw. Of fundamental importance is determining whether the majority of N2 O emitted is produced before spring thaw and then released, or if it is produced at the onset of spring thaw. It has been suggested that physical release comprises the often observed first N2 O emission event at thaw, while the subsequent event is likely due to enhanced denitrification. To test this, the objective of this study was to compare changes in soil profile N2 O content over time to N2 O surface fluxes at spring thaw measured using the micrometeorological flux‐gradient technique, which allowed for capturing of the dynamic nature of N2 O flux during thawing. Measurements were conducted from October 2010 to May 2011, in a 1.5‐ha plot (conventional till) in Ontario, Canada. Soil profile measurements included water content, temperature, and N2 O gas concentration weekly overwinter and daily during the main spring‐thaw. Soil N2 O mass in gaseous and aqueous forms was estimated. Soil N2 O mass in the 0‐ to 70‐cm profile reached a total 23 mg N2 O m ‐2 and decreased rapidly during spring thaw when two events of heightened flux occurred. During the first event, surface N2 O fluxes corresponded to 24% of the change in mass, however during the second event N2 O fluxes were five times larger. Our results provide the first quantitative evidence for the suggestion that N2 O spring thaw emission is comprised by a first event mostly due to physical release, followed by a second event with fluxes predominantly due to de novo production. The physical release event was simultaneous with large decreases in N2 O trapped in the top soil layer and not due to N2 O trapped at depth. Exact apportioning of surface flux into N2 O sources (i.e., accumulated in profile vs. newly produced) is not possible, but assuming that most of the first emission event was due to physical release gives a rough estimate of 22% for the contribution of physical release.